Characterization of a High-Affinity Copper Transporter CTR1a in the White-Nose Syndrome Causing Fungal Pathogen Pseudogymnoascus destructans - Saika Anne; Alyssa D. Friudenberg; Ryan L. Peterson (Journal of Fungi)
Copper is an essential micronutrient and the ability to scavenge tightly bound or trace levels of copper ions at the host–pathogen interface is vital for fungal proliferation in animal hosts. Recent studies suggest that trace metal ion acquisition is critical for the establishment and propagation of Pseudogymnoascus destructans, the fungal pathogen responsible for white-nose syndrome (WNS), on their bat host. However, little is known about these metal acquisition pathways in P. destructans. In this study, we report the characterization of the P. destructans high-affinity copper transporter VC83_00191 (PdCTR1a), which is implicated as a virulence factor associated with the WNS disease state. Using Saccharomyces cerevisiae as a recombinant expression host, we find that PdCTR1a can efficiently traffic Cu ions into the yeast cytoplasm. Complementary studies in the native P. destructans fungus provide evidence that PdCTR1a transcripts and protein levels are dictated by Cu-bioavailability in the growth media. Our study demonstrates that PdCTR1a is a functional high-affinity copper transporter and is relevant to Cu homeostasis pathways in P. destructans.